Hope of life of people with cancer accompanied by Primary Health Care (Research, Society and Development, 2021)
The hope has an amazing impact how the pacient deal his physical, emotions and spirituals problems. Thus, can to perceive that the hope gives forces to pacientes fighting against their condicion. The objective was to quantify the people’s hope in treatement or pursuance of cancer followed for the primary health care system in the city of Lagarto, Sergipe. This was a crosssectional, exploratory, quantitative study involving descriptive and analytical approaches. Data were collected  through interviews with individuals diagnosed with cancer through holp instrument of avaliation, Herth Hope Scale (HHS). The study sample comprised 42 cancer people, 47,6% in oncological treatment and 52,4% in accompaniment. The middle score in Herth Hope Scale was 40,59, that mean an high level of hope, mainly when the hope is associated with spirituality/religiosity. It is important to know what impacts harmfully in variables about hope to improve the quality of life, since the hope helps for only process of coping with cancer.